Establishing diagnostic strategies for cannabis allergy. (3rd October 2022) - Toscano, Alessandro; Elst, Jessy; van der Poorten, Marie-Line; Beyens, Michiel; Heremans, Kevin; Decuyper, Ine I.; Van Gasse, Athina L.; Mertens, Christel; Van Houdt, Michel; Hagendorens, Margo M.; Sabato, Vito; Ebo, Didier G.
ABSTRACT: Introduction: Cannabis is the most widely consumed illicit drug in the world and carries a risk of severe IgE-mediated allergic reactions, requiring appropriate diagnostic management. Currently available diagnostics are still relatively limited and require careful interpretation of results to avoid harmful over- and underdiagnosis. Areas covered: This review focuses on the most up-to-date understandings of cannabis allergy diagnosis, starting with the main clinical features of the disease and the allergenic characteristics of Cannabis sativa, and then providing insights into in vivo, in vitro, and ex vivo diagnostic tests. Expert opinion: At present, the diagnosis of IgE-mediated cannabis allergy is based on a three-step approach that starts with accurate history taking and ends with a confirmation of sensitization to the whole extract and, finally, molecular components. Although much has been discovered since its first description in 1971, the diagnosis of cannabis allergy still has many unmet needs. The lack of commercial standardized and validated extracts and in vitro assays makes a harmonized workup of cannabis allergy difficult. Furthermore, the epidemiological characteristics, and clinical implications of sensitization to different molecular components are not yet fully known. Future research will complete the picture and likely result in an individualized and standardized approach.